Implementation of attached growth system in Malaysia: An overview - Hayder G.; Mohamad FuAd N.F.S.B.; Perumulselum P.A.L. (CRC Press/Balkema, 2023)
Offshore oil well production; Slags; Attached growth; Attached growth systems; Malaysia; Treatment process; Wastewater treatment